Simultaneous SO2 Removal by Wastewater with NH3 - Ipek, Ubeyde; Ekinci, Mehtap; Arslan, E. Isil; Cuci, Yakup; Hasar, Halil (Springer, 2009)
Sulfur dioxide (SO2) is basically resulted from emission of fossil fuel. The ammonia washing is of methods used to remove SO2 from fuel gas. Several wastewaters contain high ammonia concentrations causing the various problems at wastewater treatment or receiving environment. The synthetic wastewater containing NH3 was sprayed down as flue gas moved up in the scrubber so that it could be a reaction between SO2 and NH3. The effect of NH3 concentration and pH on SO2 removal was determined. SO2 was decreased from about 1,000 to 0, 36, 49 and 66 ppm at NH3 concentrations of 328, 88, 32 and 9 mg l(-1), respectively. While SO2 of 1,000 ppm was completely treated at 328 mg NH3 l(-1), pH was around 7.16 at the end of process. Consequently, it was recognized that this process could be used for both the SO2 removal and the wastewater neutralization.
Keywords: Sulfur dioxide; Ammonia; SO2 scrubbing; Wastewater